Oxidative status and antioxidant enzyme levels in deep venous thrombosis patients - Turker, Fevzi Sarper; Malbora, Ayse; Erisir, Mine (E-Century Publishing Corp, 2021)
Deep vein thrombosis (DVT), a subset of venous thromboembolism (VTE), is a major preventable cause of morbidity and mortality worldwide. We aim to investigate changes in oxidative injury markers and the levels of antioxidant parameters in DVT patients. 50 DVT patients who were admitted to the cardiovascular surgery clinic with acute (<2 weeks) or chronic (>= 4 weeks) DVT and 100 healthy individuals were included. As oxidative injury marker malondialdehyde and the antioxidant parameters including reduced glutathione, glutathione peroxidase, catalase, and superoxide dismutase were analysed in the collected peripheral blood samples. Demographic characteristics of the acute and chronic DVT patients were similar (P>0.05). In all DVT patients having thrombosis in the distal and proximal leg veins the mean malondialdehyde and glutathione peroxidase activity were significantly increased, but superoxide dismutase activity significantly decreased, compared to the healthy controls (P<0.05). No difference was observed between distal and proximal DVT patient groups. The increased levels of malondialdehyde in our study is considered to result from the significant decrease in the antioxidant enzyme activity of superoxide dismutase. Furthermore, we are of the opinion that the increased levels of glutathione peroxidase enzyme activity observed in all patients could not compensate the reduction in the superoxide dismutase activity, thereby being insufficient in preventing the increase in the malondialdehyde levels.
Keywords: DVT; SOD; vein thrombosis; oxidative damage; MDA